South Africa's proposed new Marine Protected Area around the Prince Edward Islands: an analysis of legal obligations, options and opportunities - Nel, Deon C (Institute of Marine and Environmental Law, 2025)
In June 2004, the South African Minister of Environmental Affairs and Tourism, Minister van Schalkwyk, announced South Africa's intention to declare one of the largest MPAs in the world around its sub-Antarctic Prince Edward Islands. It was clear from the announcement that the objective of the proposed MPA was for both fisheries management purposes as well as conservation of marine ecosystems and biodiversity in the area. As a first step the Minister announced that the current “no-fishing” zone would be extended from 8 to 12 nautical miles. This was done a few months later by means of an amendment to fishing regulations for licensed South African vessels fishing for Patagonian toothfish Dissostichus eleginoides. This announcement followed South Africa's recent declaration of four new MPAs along its continental coastline, bringing the proportion of its coastline under MPA protection to 18%. These developments are consistent with international efforts1 to increase the proportion of marine habitats under formal protection, and follow a greater appreciation over the last decade for the role that MPAs can play in both fisheries management and conservation of marine ecosystems.